The Use Of Mediation In Maritime And Fisheries Dispute Resolution - Sabela Gayo (Legalpreneur Journal, 2023)
AbstractThe sea is one of the boundaries between countries and is one of the sources of income and life of a nation, Marine Management provides benefits that are so great that all parties orcountries want to explore and exploit these resources, including the high seas, so thatsometimes it causes disputes between partiesincluding between countries in carrying outits management. Disputes that occur can be resolved nationally or internationally,depending on the parties to the dispute in it. Internationally, the settlement of fisheriesdisputes that occur at sea can be resolved peacefully between the two parties, but if apeaceful agreement between the parties cannot be reached , then the procedure forresolving fisheries disputes at sea can be done by mediation methods, namely cooperativemaritime diplomacy, persuasive maritime diplomacy and coercive maritime diplomacy.Keywords: Alternative Dispute Resolution, Marine, Fisheries